Energy-efficient medium access control strategy for cooperative wireless networks - Sami, Mahmoud (2016)
Green communication has recently gained much attention, as it not only guarantees Quality of Service (QoS) and minimizes cost and energy consumption, but it is also environmentally benign. The paradigm shift toward energy-efficient communication has newly intensified in various technical approaches. Cooperative communication has been introduced as an effective, energy-efficient transmission technique, in which the single antenna nodes are encouraged to share their resources and construct a virtual Multi Input Multi Output (MIMO) system, resulting in higher diversity gain and throughput. Cooperative communication is considered as an efficient solution for mobile nodes where some difficulties in terms of physical size and energy consumption arise from implanting multiple antennas. However, the benefits of cooperative communication would be degraded by traditional, higher layer protocols designed for legacy non-cooperative systems. Thus, considering the impact of cooperation on higher layers and designing a MAC protocol are essential. This study introduces a new cooperative MAC protocol called EAP-CMAC (Energy Aware Physical-layer Network Coding Cooperative MAC) that integrates cooperative communication into PNC in wireless ad-hoc networks. In EAP-CMAC, the best transmission mode is selected among direct transmission, traditional cooperation and PNC-based transmission by considering the destination queue and source-destination link quality.Moreover, a joint relay selection and power allocation algorithm is proposed based on location information and the nodes residual energy that significantly improves the network lifetime and energy saving in wireless networks. The simulation results indicate that EAP-CMAC outperforms IEEE 802.11 and CoopMAC in terms of energy-efficiency by 35% and 100% respectively. Furthermore, the proposed optimal power allocation enhances EAP-CMAC performance in terms of network lifetime by 7% compared to equal power allocation.Moreover in this study a cooperative Medium Access Control (MAC) protocol, called Cooperative Cognitive TDMA (CC-TDMA), is proposed for cognitive networks. The proposed protocol decides between energy harvesting, data transmission and relaying transmission. In this regard, licensed users lease part of their spectrum to unlicensedusers to retransmit the failed packets on the licensed users' behalf. By doing so, the unlicensed users obtain greater opportunity for data transmission, thus increasing their performance. The simulation and analytical results indicate that the CC-TDMA significantly improves the throughput and Packet Drop Rate (PDR) of both licensed and unlicensed users compared to conventional TDMA.